Students learning styles: implication on understanding and knowledge retention / Raihana Hanis Husshin - Husshin, Raihana Hanis (2012)
Learning styles can be defined as the preferred ways of learning process an individual practices and applies according to their understanding level. Basically, every individual people have different learning style. The aim of this study were to identify UiTM final year pharmacy students’ preferred learning styles, to investigate pharmacy students’ perception on impact of learning styles on knowledge retention, and to identify relationship between learning styles and knowledge retention. This study is a crosssectional quantitative study conducted among final year students in Faculty of Pharmacy, UiTM, with a set of self-developed questionnaire and a set of Grasha Riechmann style of learning interaction model as a standard. Cumulative Grade Point Average (CGPA) was used to objectively measure knowledge retention due to time constraints in this study. There was significant in this analysis, F (2, 87) =3.24, p=0.044. Group of students which is excellent in academic performance is more likely to learn by listening to lectures. Findings show that there are similarities between the self-developed questionnaire and the Grasha Riechmann style of learning interaction model. This study summarizes recent studies and report new data supporting the conclusion that individual learning style give implication on understanding and knowledge retention. This study can contribute to further findings and conclusion for educational development.